Utilization of Social Media by Government Institutions to Enhance Digital Public Participation in Addressing the Free Nutritious Food (MBG) Hoax Issue - Swastiningsih Swastiningsih; Gatot Repli Handoko; Heru Yulianto (SOSIOEDUKASI, 2025)
Social media has transformed public interaction between governments and citizens, making it a vital tool for digital participation in policymaking. However, it has also enabled the spread of misinformation, especially regarding government initiatives like Indonesia's Free Nutritious Meals (MBG) program, which faced false claims about food safety and cancellations. This study explores how government institutions use social media to enhance public engagement in combating such misinformation. Through a qualitative approach, the research examines existing literature on government social media use and digital participation strategies, focusing on the MBG hoax case. The findings show that while government social media is effective for information dissemination, it lacks deeper public interaction. The study emphasizes the need for more transparent communication, timely responses, and participatory content creation. It concludes with recommendations to improve institutional coordination, citizen engagement, and media literacy efforts to better counter misinformation.